Effects of Irrigation and Fertilization on the Morphophysiological Traits of Populus sibirica Hort. Ex Tausch and Ulmus pumila L. in the Semiarid Steppe Region of Mongolia - Ser-Oddamba Byambadorj (MDPI AG, 2021)
Desertification is impeding the implementation of reforestation efforts in Mongolia. Many of these efforts have been unsuccessful due to a lack of technical knowledge on water and nutrient management strategies, limited financial support, and short-lived rainfall events. We investigated the effects of irrigation and fertilization on the morphophysiological traits of Populus sibirica Hort. Ex Tausch and Ulmus pumila L. and to suggest irrigation and fertilization strategies for reforestation. Different irrigation and fertilizer treatments were applied: no irrigation, 2 L h−1, 4 L h−1, and 8 L h−1 of water; no fertilizer, 2 L h−1 + NPK, 4 L h−1 + NPK, and 8 L h−1 + NPK; and no compost, 2 L h−1 + compost, 4 L h−1 + compost, and 8 L h−1 + compost. The leaf area (LA) and specific leaf area (SLA) of both species responded positively to 4 and 8 L h−1. Results also showed that the addition of either NPK or compost to 4 or 8 L h−1 irrigation resulted in a higher LA, SLA, and leaf biomass (LB). Total chlorophyll content decreased with irrigation in both species. The same pattern was detected when a higher amount of irrigation was combined with fertilizers. Lastly, we found that both diurnal and seasonal leaf water potential of plants grown in 4 or 8 L h−1 were significantly higher than those of plants grown in control plots. Therefore, 4 or 8 L h−1 with either NPK or compost has shown to be the optimal irrigation and fertilization strategy for the species in an arid and semiarid region of Mongolia. Results should provide us with a better understanding of tree responses to varying amounts of irrigation with or without fertilizer in pursuit of sustainable forest management in arid and semiarid ecosystems.